(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
The Gamebadges project is developing the first Europe-wide, competence-based Open Badge ecosystem tailored to the needs of the game industry and game education. The ecosystem consists of a publicly available Competence Map and more than 400 digital badges across three levels (Bronze, Silver, and Gold). It is implemented by a consortium of nine partner organizations from five European countries, combining expertise from vocational education and training (VET), higher education, and professional game development. A central aim of the project is to harmonize job titles and related skill sets across a young industry. The badges are designed to complement portfolios and résumés by adding structured, criteria-based competence validation grounded in documented evidence. While the ecosystem serves both educational institutions and companies, this paper focuses on the industry perspective, where badge-based recognition is still emerging and raises specific structural and cultural questions. Opportunities and Strengths From an industry standpoint, the ecosystem offers several strategic advantages: Recognition of Prior Learning (RPL): Supports validation of informal, self-directed, and work-based learning. Cross-border transparency: Enables shared visibility of competences in a mobile, project-based sector. Shared terminology: Creates a common language for skills that are often implicit or interpreted differently across companies and regions. Evidence-based validation: Allows professionals to use prior work (when shareable) as structured evidence aligned with defined competence criteria. Career development pathways: Connects competence levels to training, feedback, and progression from Bronze to Silver, and Gold. Enhanced professional profiles: Adds standardized, transparent validation alongside portfolios, and résumés. Together, these elements aim to lower structural and cultural barriers across Europe and support labor mobility within the creative technology sector. Key Challenges and Open Questions At the same time, implementing a large-scale professional badge ecosystem introduces significant tensions: Trust and distance: Validation becomes complex when evaluators and applicants lack shared context or direct interaction. Confidentiality constraints: Internal company materials (NDA protected) may not be shareable as evidence. Platform and scalability limits: Many badge platforms were not designed for decentralized, cross-organizational ecosystems. System integration: Companies may already have internal performance evaluation systems, leading to redundancy or misalignment. Gold-level recognition: Motivating highly experienced professionals to apply for formal recognition can be difficult if the added value is unclear. Quality Assurance and Professional Progression A central theme in the conference discussion was quality assurance (QA). When participants were asked whether a 100 percent reliable and fully credible competence validation system is possible, no one indicated agreement. This suggests a crucial insight: a certain degree of uncertainty is inherent in all assessment systems. Rather than pursuing absolute certainty, credibility must be built through transparency, shared criteria, documented evidence, and iterative improvement. An additional perspective emerged in the discussion of the Bronze—Silver—Gold structure. Rather than functioning as a competitive ranking, the levels were understood as markers of progression from peripheral participation toward recognized expertise. In this sense, badges make professional growth visible and provide meaningful milestones along a developmental path. A related concern was also raised regarding the large number of badges, which may increase the overall complexity of the ecosystem. Proof of Concept and Research Trajectory The Gamebadges initiative (2024-2026) is currently in a proof-of-concept phase, focusing on piloting, iterative refinement, and data collection. The objective is to identify and evaluate best practices for transparent, credible, and scalable badge-based competence recognition in professional environments. Findings from ongoing trials will inform the next development stage and contribute to broader discussions on the design and quality assurance of emerging credentialing ecosystems. Researchers, educators, and industry stakeholders interested in further information or collaboration are welcome to contact the authors through the website at gamebadges.eu. Keywords: Open Badges, micro-credentials, quality assurance competence validation, game industry